Adherence to Medications after Hospital Discharge in the Elderly. (26th March 2013) - Mulhem, Elie; Lick, David; Varughese, Jobin; Barton, Eithne; Ripley, Trevor; Haveman, Joanna
Abstract : Objectives . To evaluate the adherence rate to prescribed medications in elderly patients 24–48 hours after being discharged from the hospital. Methods . Family medicine residents visited patients over the age of 65 years at their homes one to two days after being discharged from the hospital and documented all the medications that they were taking since coming home from the hospital. The list of medications was later compared to the medications recorded in hospital discharge instructions. Results . Complete data was available for 46 participants. The average patient age was 76 years; 54.4% were women. Only three patients (6.5%) adhered completely to the discharge medication list found in the medical record. Thirty-six patients (78.2%) reported taking at least one additional prescription medication, twenty patients (43.4%) missed at least one prescription medication, twenty patients (43.4%) reported taking the wrong dose of at least one medication, and nineteen patients (41.3%) reported taking medications at an incorrect frequency. Conclusion . The vast majority of elderly patients in our study did not adhere to the medication regimen in the first two days after hospital discharge. Cost-effective improvements to hospital discharge processes are needed to improve adherence and reduce preventable posthospitalization complications.